Two new Eunotia species (Eunotiaceae, Bacillariophyta) from the Yangambi Biosphere Reserve, Democratic Republic of the Congo - Taylor, Jonathan C.; Cocquyt, Christine (Phytotaxa, 2025)
Species in the genus Eunotia commonly occur in waters with acidic to circumneutral pH, low nutrient content, and low dissolved salt concentrations. The genus is also commonly encountered worldwide in dystrophic habitats with high humic acid content. Taxa from this genus are considered to be sensitive to pollution and indicators of good water quality. The Democratic Republic of the Congo, with its remaining tropical forest, has many such waterbodies. Small forest streams support a great diversity of diatoms and Eunotia in particular. These water bodies are often at risk from multiple potential impacts. Documenting and describing diatom species and community structure is important to potentially show future change and aid in developing possible management strategies. Based on a number of investigations in the Yangambi Biosphere Reserve, we describe two new species of Eunotia from tropical forest streams: Eunotia tropicaesilvae sp. nov. and Eunotia marginepunctata sp. nov.